2022
DOI: 10.1212/con.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Obstetric Anesthesia

Abstract: PURPOSE OF REVIEW: The advantages of neuraxial anesthesia over general anesthesia in the obstetric population are well established. Some neurologic conditions have the potential to lower the safety threshold for administration of neuraxial anesthesia, whereas others require special consideration before using general anesthesia. The aim of this article is to help neurologists determine when neuraxial anesthesia can be safely administered and when it is inadvisable.RECENT FINDINGS: Neuraxial anesthesia can usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…As this is a diagnosis of exclusion, neuroimaging was performed to exclude alternative causes. For more information on spread of anesthetic in pregnant women, refer to the article “Neurologic Complications of Obstetric Anesthesia” by Janet F. R. Waters, MD, MBA, FAAN, 56 in this issue of Continuum .…”
Section: Other Eye and Facial Symptomsmentioning
confidence: 99%
“…As this is a diagnosis of exclusion, neuroimaging was performed to exclude alternative causes. For more information on spread of anesthetic in pregnant women, refer to the article “Neurologic Complications of Obstetric Anesthesia” by Janet F. R. Waters, MD, MBA, FAAN, 56 in this issue of Continuum .…”
Section: Other Eye and Facial Symptomsmentioning
confidence: 99%
“…Multiple prior case series have suggested that baseline neurologic symptoms of patients with pre-existing spinal canal pathology or nerve injury may worsen after neuraxial anesthesia or analgesia (28)(29)(30). However, neuraxial anesthesia can usually be administered safely in most patients with neurologic disease (31). The decision to administer neuraxial anesthetics in patients should be based on risk-to-benefit considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Physiopathologically, there are multiple complications of neurological origin that can arise after spinal anesthesia. To do this, we must know the three mechanisms by which a peripheral nerve can suffer an injury [3].…”
Section: Pathophysiology Of Neurological Complicationsmentioning
confidence: 99%